Perancangan Sistem Smart Farming Berbasis Internet of Things (IoT) Menggunakan Node-Mcu Dan Sensor Suhu Pada Peternakan Ayam Gibran Farm - Azzahro Nurhabibah; Ahmad Aftah Syukron (Riau Jurnal Teknik Informatika, 2026)
Laying hen farming is a business sector that requires optimal management of the coop environment to support the health and productivity of the chickens. This study aims to design an Internet of Things (IoT)-based automatic lighting system for laying hen houses at Gibran Farm using a NodeMCU ESP32 and a DHT22 sensor. The main problem in the farm is the manual operation of the cage lights, resulting in unstable cage temperatures and impacting chicken productivity. The research methods include observation, system design, tool assembly, programming, and testing. The system works by detecting the cage temperature in real time through a DHT22 sensor, then the NodeMCU ESP32 automatically controls the lights according to predetermined temperature limits. The results show that the system is able to monitor temperature and control cage lighting effectively. This system also helps maintain stable cage temperatures and increases the efficiency of electrical energy use.